Clinical Significance of Microbleeds in Subcortical Vascular Dementia - Won Seo, Sang; Hwa Lee, Byung; Kim, Eun-Joo; Chin, Juhee; Sun Cho, Yoon; Yoon, Uicheul (Stroke (1970), 2007)
Background and Purpose— Despite many studies investigating the association between the ischemic changes and cognitive impairment in subcortical vascular dementia (SVaD), few studies correlated cognitive impairment with microbleeds (MBs) frequently seen in SVaD. Methods— Participants consisted of 86 patients with SVaD who fulfilled the criteria proposed by Erkinjuntti et al. Results— MBs occurred in 73 of 86 (84.9%) patients with SVaD. MBs were most commonly distributed in the cortex, and the cortical MBs were most pronounced in the temporoparietal area. A multiple regression showed that the number of cerebral MB was an independent predictor of cognitive impairment in multiple domains and the severity of dementia even after controlling confounding factors such as age, education, ischemic severity, and number of lacunes. Conclusion— These results indicate that cerebral MB is one of the important factors that cause cognitive impairments in SVaD.